centralization and decentralization in Iraq and its future prospects - سيد, د.محمد محسن (Journal of Planner and Development, 2011)
Centralization and decentralization, planning and development, and community participation in the management of its affairs and to activate all the abilities that multiple methods aimed at creating the proper environment for the growth and development of society in the place where he lives. As long as the overall trend in Iraq, represented by the Permanent Constitution of decentralization to regions and provinces, the solutions to the obstacles that may face this transition in some respects presents ways of coordination and integration between multiple levels of planning which can be exercised by the schematic in the future the organization. In this paper some of the visions and ideas that can  contribute to the organization.